The panel threshold analysis of digitalization on manufacturing industry’s green total factor productivity - Lu Liu; Yulong Xin; Bei Liu; Yuankui Pang; Weiran Kong (Scientific Reports)
Abstract Green and sustainable development of manufacturing industry has become the developing trend, and green total factor productivity is an important indicator for measuring the green growth of the manufacturing industry. The rapid development of digitalization provides new opportunities for the improvement of manufacturing industry’s green total factor productivity (IGTFP). However, there exists two different perspectives of “digital promotion effect” and “digital inhibition effect” presently, which causes “digital paradox”. That is, digitalization may have a non-linear effect on IGTFP. Therefore, this study focuses on the industry level and aims to test the threshold impact of digitalization on IGTFP. Furthermore, this study tries to explore the boundary conditions and applicability of the green driving effect of digitalization on sub-industries from the perspective of heterogeneous technological innovation abilities in different industries. The empirical study is based on the panel data of 29 manufacturing industries in China 2012–2019. The empirical results show that: (1) Digitalization has a significant threshold impact on IGTFP, and the research results are still robust according to changing the threshold variable algorithm and carrying on a Winsorize test. (2) Industry technological innovation (ITI) plays a threshold role in the process of digitalization impact on IGTFP. (3) Heterogeneity analysis shows that the impact mechanism varies depending on differentiated industry factor intensity and industry pollution degree. Therefore, policymakers should formulate differentiated industry digitalization strategies.